ANALISIS PENERAPAN STANDAR DOKUMENTASI KEPERAWATAN DENGAN KUALITAS PELAYANAN KEPERAWATAN DI RUANG RAWAT INAP RSUD GAMBIRAN - Efendy, Mohamad As’ad (STRADA : Jurnal Ilmiah Kesehatan, 2017)
Charging nursing documentation that does not comply with the standards may lead to differences in the action by another nurse, causing a decline in service quality. The purpose of this study was to analyze the relationship of standard implementation of nursing documentation with quality nursing care in patient room of hospitals Gambiran. The study design was a cross sectional correlation. Population studied all nurses in inpatient hospitals Gambiran Kediri, amounting to 259 people, with a purposive sampling technique was obtained samples are 54 respondents. Independent variable is the standard implementation of nursing documentation, while the dependent variable is the quality of nursing care. Analysis of data using phi correlation test. mentation, ie 40 respondents (74.1%) and the majority of respondents rate the quality of nursing services in both categories, namely 36 respondents (66.7%). Nursing documentation influence on the speed of service, but not many patients are aware of this condition, so there are few respondents who did not properly apply the nursing documentation but can lead to patient satisfaction, although not having a strong relationship but implementation remains documentation standards implemented as a means of communication for nurses and responsibilities and legal proof